EFEKTIVITAS SIFAT BAKTERIOSTATIK Porphyromonas Gingivalis DAN Lactobacillus Acidophilus SEBAGAI KONTROL BIOLOGI PERTUMBUHAN Candida Albicans DALAM BERBAGAI PH SALIVA BUATAN - Basri A. Gani; Abdillah Imron Nasution; Ridha Andayani; Vivi Zayanti; Ratih Asrina Fitri (Dentistry Faculty, 2016)
AbstractOral candidiasis caused by Candida albicans as a result of an imbalance of oral biology activities, preventive therapy with using chemical, biological as well one of them to increasing the effectiveness of the role of the bacteriostatic properties of normal oral flora such as Lactobacillus species and Porphyromonas species that helps maintain the regulation of carbohydrate fermentation activity of saliva in the form acid and alkaline pH. The purpose of this study evaluated the effectiveness of the bacteriostatic properties of P. gingivalis and L. Acidophilus in influencing the growth of C. albicans. While the materials used in this study are C. albicans and L. acidophilus strains of the laboratory, P. gingivalis ATCC 33 277 and artificial saliva. The results obtained by the method of SDA and NA media culture, pH saliva test interactions, the calculation of the bacteria colony by colony counter, and a slide culture for C. albicans. The results showed a change leads to an alkaline pH of saliva after interacted by C. albicans with P. gingivalis (p 0.05) and C. albicans with L. acidophilus (p 0.05) using pH control of 4,5,6,7,8, and 9. Further, the colony of P. gingivalis growth is more dominant compared to C. albicans (p 0.05), but on the contrary, C. albicans colonies growth was more dominant than the L. acidophilus (p 0.05). Nevertheless, the those bacteria are capable of inhibiting the growth of hypha from C. albicans as a virulence factor that most affects the host mucosal infection. From the research results can be concluded that the interaction of C. albicans, P. gingivalis and L. acidophilus in artificial saliva can increase the degree leading to an alkaline pH, while P. gingivalis and L. acidophilus can be reduced of colonies of C. albicans hypha and able to inhibit the growth of C. albicans. Nevertheless, both bacteria can be bacteriostatical against C. albicans.Keywords: Candida albicans, Porphyromonas gingivalis, Lactobacillus acidophilus, saliva pH and Oral candidiasis